2008
DOI: 10.1159/000126492
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Morphology and Aerobic Capacity in Patients with Obstructive Sleep Apnoea Syndrome

Abstract: Background: Despite the fact that patients with obstructive sleep apnoea syndrome (OSAS) often have symptoms at the level of skeletal muscle such as fatigue, the question of whether the structural, cellular and functional properties of limb skeletal muscles are affected has not been fully examined. Objective: The aim was to examine physiological and muscular parameters in patients with OSAS and to assess the relationship between these parameters and the clinical symptoms. Method: Eighteen patients with OSAS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 88 publications
2
30
3
1
Order By: Relevance
“…14 Muscle biopsy studies have demonstrated structural and bioenergetic changes in skeletal muscle fiber in OSA subjects, 27 as well as increased microvascularization in skeletal muscle, 11 similar to changes observed in other states of chronic hypoxia. Several studies have demonstrated an abnormal cardiovascular response during exercise or recovery in OSA patients, including increased diastolic blood pressure, decreased stroke volume, attenuated heart rate during peak exercise and recovery, and global ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…14 Muscle biopsy studies have demonstrated structural and bioenergetic changes in skeletal muscle fiber in OSA subjects, 27 as well as increased microvascularization in skeletal muscle, 11 similar to changes observed in other states of chronic hypoxia. Several studies have demonstrated an abnormal cardiovascular response during exercise or recovery in OSA patients, including increased diastolic blood pressure, decreased stroke volume, attenuated heart rate during peak exercise and recovery, and global ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 83%
“…[8][9][10] The impact of OSA on exercise capacity remains unclear. Prior studies examining exercise capacity in OSA patients have yielded confl icting results, with some demonstrating reduced exercise capacity [11][12][13][14][15][16] and others suggesting exercise capacity is not impaired. [8][9][10]17,18 These studies have several methodological limitations that make reconciling their fi ndings challenging.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 2 more Smart Citations
“…Parafaringeal kas dokusuna yönelik yapılan çalış-malarda horlayanlarda orta faringeal konstrüktör kaslarda tip 2a fiberlerinin yüzdesinin anlamlı ölçüde arttığı gösterilmiştir. Elektrofizyolojik olarakta üst havayolu kaslarında değişikler saptanmıştır (16)(17)(18) . Çalışmamızda, UAS pozitif grup ile negatif kontrol grubunu karşılaştırdığımızda parafaringeal duvar kalınlığının anlamlı ölçüde artmış olarak bulduk.…”
Section: Discussionunclassified